Correction: Krause et al. Higher Order Thinking by Setting and Debriefing Tasks in Dutch Geography Lessons. Eur. J. Investig. Health Psychol. Educ. 2022, 12, 11-27 - Uwe Krause; Tine Béneker; Jan van Tartwijk (MDPI AG, 2022)
In the original publication [...]